Validação relativa de Questionário de Freqüência Alimentar em gestantes usuárias de serviços do Sistema Único de Saúde em dois municípios no Rio Grande do Sul, Brasil Validation of a Food Frequency Questionnaire conducted among pregnant women attended by the Brazilian National Health Service, in two municipalities of the State of Rio Grande do Sul, Brazil - Andressa Giacomello; Maria Inês Schmidt; Maria Angélica Antunes Nunes; Bruce Bartholow Duncan; Rafael Marques Soares; Patrícia Manzolli; Suzi Camey (Instituto Materno Infantil de Pernambuco, 2008)
OBJETIVOS: avaliar o desempenho do Questionário de Frequência Alimentar (QFA), desenvolvido por Sichieri e Everhart, em medir o consumo alimentar de gestantes atendidas pelo Sistema Único de Saúde (SUS), comparando as estimativas de consumo de energia e nutrientes com as obtidas por recordatórios alimentares. MÉTODOS: foram realizadas duas entrevistas com gestantes em atendimento pré-natal em Bento Gonçalves e Porto Alegre, no Rio Grande do Sul, Brasil. Na primeira, foi aplicado o QFA e, depois, os recordatórios alimentares relativos aos dois dias prévios. Na segunda, foram obtidos novos recordatórios. Médias e limites de concordância para as diferenças entre as duas avaliações de ingestão alimentar foram calculadas conforme Bland-Altman. RESULTADOS: a diferença entre os métodos mostrou que o QFA superestimou o consumo de energia e nutrientes. O coeficiente de correlação ajustado para energia variou de 0,01 (gordura insaturada) a 0,47 (cálcio). Correlações maiores foram observadas para fibras, vitamina C, ácido fólico, cálcio e potássio. Em média, 30% das gestantes foram classificadas no mesmo quartil de consumo. CONCLUSÕES: o QFA pode ser uma ferramenta útil para avaliar consumo de gestantes em estudos epidemiológicos, contanto que sejam realizados esforços para melhorar seu desempenho. É necessário avaliar a influência de características sócio-demográficas e estado de saúde na validade do método. OBJECTIVES: to evaluate a Food Frequency Questionnaire (FFQ) previously designed by Sichieri and Everhart to provide information about food consumption among pregnant women attended by the Brazilian National Health Service. To compare the mean daily intakes of energy and nutrients as assessed using a FFQ and dietary recalls. METHODS: the study took place in two cities: Bento Gonçalves and Porto Alegre, State of Rio Grande do Sul, Brazil. During a first interview, the FFQ was administered to pregnant women, followed by two dietary recalls. In a second interview two further food recalls were obtained. The Bland-Altman analysis was used to assess the degree of agreement between the FFQ and dietary recalls. RESULTS: the FFQ produced higher energy and nutrient intakes. The correlation coefficient between nutrient intake measured using dietary recalls and using the questionnaire, after adjusting for energy intake, ranged from 0.1 (unsaturated fat) to 0.47 (calcium). The nutrients: fiber, Vitamin C, folate, calcium and potassium showed higher coefficients (above 0.4). Thirty percent of individuals were classified by the two dietary assessment methods into the same quartile. CONCLUSION: this FFQ is a useful tool for epidemiological studies among pregnant women; although efforts need to be made to improve its performance. More studies are necessary to identify sociocultural and behavioural factors that influence its validity.